DAMPAK DIPLOMASI PUBLIK KOREA SELATAN MELALUI KOREAN WAVE TERHADAP PERKEMBANGAN PASAR E-COMMERCE LOKAL INDONESIA - Zalwa Apriliana Sesa (2023)
This research explains and analyzes the impact of South Korea's implementation of public diplomacy by utilizing the Korean Wave on the development of Indonesia's local e-commerce market. South Korea is one of the major powers in the East Asian region that created and utilized the Korean Wave as its diplomatic strategy. Through the involvement of K-pop idols and Korean actors/actresses in promoting South Korean culture, foreign communities can be more open in accepting and consuming Korean culture. The increased interest of foreign fans and communities in South Korean culture then becomes an opportunity for local Indonesian e-commerce to capitalize on the Korean Wave and improve company performance. Tokopedia, Bukalapak, and Blibli are Indonesian marketplaces that successfully collaborate with Korean Wave stars as the company's Brand Ambassadors. In this research, the author uses the concept of public diplomacy to analyze South Korea's diplomatic activities in Indonesia through the Korean Wave. In addition, the concept of e-commerce is also used by the author to identify the types of digital economy companies that are going through the growth process. The research method used is descriptive qualitative through interviews and review of official documents then presented descriptively. The results of this study show that Indonesian local e-commerce has experienced market development in terms of increased site visits, company revenue, and Initial Public Offering (IPO) of local e-commerce companies on the Indonesia Stock Exchange (IDX) after utilizing the popularity of the Korean Wave as an impact of South Korea's public diplomacy in Indonesia. Keywords: Public diplomacy, Korean Wave, Indonesian E-commerce, Market Development